European Masters. (London : Marlborough Fine Art Ltd., 1970)
Bacon, Francis ; Balla, Giacomo ; Bonnard, Pierre ; Boudin, Eugène ; Braque, Georges ; Cézanne, Paul ; Chagall, Marc ; Corot, Jean-Baptiste Camille ; Degas, Edgar ; Delaunay, Robert ; Derain, André ; Dubuffet, Jean ; Dunoyer de Segonzac, André ; Ensor, James ; Ernst, Max ; Feininger, Lyonel ; Friesz, Othon ; Giannattasio, Ugo ; Gleizes, Albert ; Goncharova, Natalia ; Kandinsky, Wassily ; Kirchner, Ernst Ludwig ; Kokoschka, Oskar ; Lépine, Stanislas ; Miro, Joan ; Mondriaan, Piet ; Monet, Claude ; Moore, Henry ; Nicholson, Ben ; Nolde, Emil ; Picasso, Pablo ; Pissarro, Camille ; Redon, Odilon ; Renoir, Pierre-Auguste ; Rouault, Georges ; Rousseau, Henri ; Schiele, Egon ; Seurat, Georges ; Sisley, Alfred ; Soutine, Chaim ; de Staël, Nicolas ; Sutherland, Graham ; de Vlaminck, Maurice ; Vuillard, Edouard
geboortedata per kunstenaar
Engels
European Masters, Marlborough Fine Art Ltd., London, 1970
boek